Selected papers from the 4th International Conference of the performance Measurement Association, Edinburgh, July 2004 - Radnor, Z. J. (Zoe J.); Kennerley, Mike (International journal of productivity and performance management, 2005)
Significant e-book of papers emanating from Performance Measurement and Management: Public and Private, the 4th International Conference of the Performance Measurement Association (PMA), Edinburgh, July 2004. The conference attracted over 300 delegates from 40 countries hearing presentations on issues as wide ranging as public sector performance, intangible assets and intellectual capital, as well as the design, implementation and use of measurement systems. As the title suggests the conference sought to share and exchange knowledge and insights gained in the Public and Private Sectors identi.